Pengolahan dan Pemanfaatan Sisa Serbuk Pengrajin Kayu dalam Menunjang Sektor Ekonomi Lokal di Kabupaten Gowa - Filandia Rifdian; Muh Adnan; Reni Arwanda; Sity Melindah; Nur Adfirayanti Danial (PT.Mantaya Idea Batara, 2022)
Currently, wood craftsmen have a lot of fans, which is directly proportional to the number of forests and trees that are currently decreasing. Moreover, the use of wood to make boards only uses 50-70% of a tree. The rest will be waste that is simply thrown away or burned. Like the village that we carried out this activity, in Pacellekang Village, Patallassang District, Gowa Regency. In the end we chose to reprocess the remaining sawdust to make handicrafts which of course have economic value in order to create jobs. In addition, the purpose of this activity is to make the people in Pacellekang Village more creative, innovative and productive in the post-covid-19 pandemic. In this handicraft production activity, we have provided training to the public about production, to marketing through digital marketing.